An examination of the socio-political undercurrents in Mqhayi's novel Ityala lamawele - Dikeni, Clifford (African Languages and Literatures, 2016)
Mqhayi, a Xhosa writer of the early 1900's is able to deconstruct the black and white dichotomy by using the twins as depicting some characteristics of black and white culture. The dissertation thus examines the way in which Mqhayi presents this dichotomy. He manipulates literary forms in order to articulate specific cultural attitudes which were dominant then. Xhosa writers at this time, being entirely dependent on the technologies provided by the missionaries, were forced to use metaphorical devices in order to avoid heavy censorship from the missionaries who were prescriptive and would not accept any book which they considered to be political, their main interest being in books which had a religious theme. The novel, Ityala Lamawele, coincides with some of the major political moods of its time. It is fully socialized and is absorbed directly into the dominant patterns of thought, mood and outlook of the moment from which it emerges. It addresses in a very subtle manner the socio-political conditions in which the Black people found themselves.